Effect of the massage and body manipulations contained in the traditional daily bath on motor development of 830 infants beninois - DOSSOU, Sémako Gérard; LAWANI, MOHAMED MANSOUROU; Messan, Folly; YESSOUFOU, Lafiou; TIGRI, Tertutie Nawal; Houeto, Vignon Gratien (My University, 2019)
In Africa and more particularly in Benin, many cultural corporal practices are made to newborns to promote their development. Among these practices we have traditional body care that includes massage and various stretching exercises (mechanical manipulation of the body). And several conclusions of the studies carried out on the motor development of African children have put forward the hypothesis according to which these traditional bodily cares would be at the base of the motor precocity observed with the latter. It is to verify these conclusions that we set ourselves the objective of studying the effect of massage and mechanical manipulations on the motor development of 830 newborns in Benin. This longitudinal study grouped the newborns of the cities of Dangbo, Copargo, Kouandé and Comè declared apparently healthy by the head doctors of their health zones. Our results show that the group of newborns who received massage and mechanical manipulations of the body in their traditional body care acquired early motor skills (sitting, crawling, crawling, standing up and walk) before all the other two groups. And the group of newborns who only received the massage acquired all the motor skills that the newborns of the control group. This is proof that massage and mechanical manipulations of the body are the fundamental causes of the early development of Beninese infants
Keywords: Motor development; Massage; Mechanical manipulations; Motor skills; Traditional daily bath; Benin